Metagenomic next-generation sequencing of cell-free and whole-cell DNA in diagnosing central nervous system infections - Yu, Lili; Zhang, Ye; Zhou, Jiemin; Zhang, Yu; Qi, Xuejiao; Bai, Kaixuan; Lou, Zheng; Li, Yi; Xia, Han; Bu, Hui (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Central nervous system (CNS) infections pose fatal risk to patients. However, limited sample volumes of cerebrospinal fluid (CSF) and low detection efficiency seriously hindered accurate detection of pathogens using conventional methods. Methods: We evaluated the performance of metagenomics next-generation sequencing (mNGS) in diagnosing CNS infections. CSF samples from 390 patients clinically diagnosed with CNS infections were used for mNGS of cell-free DNA (cfDNA) (n =394) and whole-cell DNA (wcDNA) (n =150). Results: The sensitivity of mNGS using cfDNA was 60.2% (237/394, 95% confidence interval [CI] 55.1% to 65.0%), higher than that of mNGS using wcDNA (32.0%, 95% [CI] 24.8% to 40.2%, 48/150) and conventional methods (20.9%, 95% [CI] 16.2% to 26.5%, 54/258) (P < 0.01, respectively). Accuracy of mNGS using cfDNA in positive samples was 82.6%. Most of viral (72.6%) and mycobacterial (68.8%) pathogens were only detected by mNGS of cfDNA. Meningitis and encephalitis with Streptococcus pneumoniae infection might be more likely to result in critically ill diseases, while Human alphaherpesvirus 3 was prone to cause non-critically ill diseases. Conclusions: This is the first report on evaluating and emphasizing the importance of mNGS using CSF cfDNA in diagnosing CNS infections, and its extensive application in diagnosing CNS infections could be excepted, especially for viral and mycobacterial CNS infections.